Supply Chain Management for Enhancing Telecommunications Company Customer Loyalty Index - Dang Nguyen, Quang; Van Nguyen, Khoa; Kolosova, Olga (International Journal of Supply Chain Management, 2020)
The purpose of the study is to compare the effectiveness of supply chain management for assessing telecommunications company customer loyalty index in Russia and Vietnam. The research methodology includes a qualitative and quantitative analysis of online survey data conducted by the call centers of telecommunications companies in Russia and Vietnam in order to identify factors determining customer loyalty for these companies. A comparative analysis of the customer loyalty assessment methods showed that the use of the most popular NPS method and the supply chain management for determining factors of customer loyalty as a multidimensional construct produces similar results; however, when repeating the study with other respondents, the NPS method results may differ due to the low stability of a single determinant. The practical significance of the research is the possibility of telecommunications companies to use the data obtained in order to increase customer loyalty and strengthen customer relationships by adjusting their marketing strategies. The development of new multidimensional customer loyalty concepts, as well as the improvement of the existing ones to be adapted to a number of foreign markets, can be a promising direction for applying the supply chain management in the telecommunications company customer loyalty index. According to the results of regression analysis between the satisfaction variable and supply chain management variables, it can be understood that the variables of delivery, information sharing and cost should be more considered, because they have a greater impact on customer loyalty index.